Corrosive substances ingestion: a review. (14th September 2019) - Hall, Alan H.; Jacquemin, Denise; Henny, Danièlle; Mathieu, Laurence; Josset, Patrice; Meyer, Bernard
Abstract: Corrosive chemical substance ingestions are a major problem, especially in developing countries, but also in developed countries such as the United States, France, and Belgium. Ingestions may be deliberate as suicide attempts (mostly in adolescents and adults) or accidental (mostly in children). The results can be devastating in terms of individual suffering and disability, but also in terms of resource utilization and costs. In developing countries, outcomes may be worse because of limited medical/surgical resources. Common sequelae include gastrointestinal (GI) tract (esophagus, stomach, pylorus, and duodenum) stricture formation, GI tract perforation, and hemorrhage. Systemic effects may also occur, such as disseminated intravascular coagulation (DIC), multi-organ system failure, and sepsis. Various interventions in the acute phase to reduce the severity of injury have been attempted, but there are no large controlled clinical trials to demonstrate efficacy. Dilation therapy in various forms is commonly used for the treatment of strictures and a variety of surgical procedures including esophagectomy and delayed replacement may be required in severe corrosive injury cases.